Toxin Neutralization Efficacy of Catechin and Silymarin against Anthrax Toxins - Taskeen, Shumaila; B Rawool, Deepak; Aggarwal, Somya; Somani, Vikas; Bhatnagar, Rakesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study investigated the in-vitro toxin neutralization potential of FDA-approved polyphenols; catechin and silymarin against  anthrax lethal and edema toxin. The titration of protective antigen (PA) against a fixed concentration of LF, and EF induced a linear  dose-dependent cytotoxic effect with maximum attainable cytotoxicity at 10 μg/mL PA, and 1 μg/mL LF/EF in RAW264.7 and CHO.K1  cells. The LT and ET-induced cytotoxicity were assessed using MTT assay, and cAMP ELISA, respectively. All the tested concentrations  (100, 10, 1, 0.1 μM) of catechin and silymarin exhibited a highly significant and dose-dependent reduction in LT-induced cytotoxicity  (p
Keywords: Anthrax; cAMP; Edema toxin; Lethal toxin; MTT